2010
DOI: 10.1096/fj.10-160119
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial expression of human cytochrome P450 epoxygenases lowers blood pressure and attenuates hypertension‐induced renal injury in mice

Abstract: Renal cytochrome P450 (CYP)-derived epoxyeicosatrienoic acids (EETs) regulate sodium transport and blood pressure. Although endothelial CYP-derived EETs are potent vasodilators, their contribution to the regulation of blood pressure remains unclear. Consequently, we developed transgenic mice with endothelial expression of the human CYP2J2 and CYP2C8 epoxygenases to increase endothelial EET biosynthesis. Compared to wild-type littermate controls, an attenuated afferent arteriole constrictor response to endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
143
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 127 publications
(151 citation statements)
references
References 52 publications
8
143
0
Order By: Relevance
“…The effect of CYP2J2 may involve various mechanisms. Although Ang II clearly elevated blood pressure in this AAA model, and overexpression of CYP2J2 or s-EH inhibitor administration have been reported to lower blood pressure ( 7,8,11 ), it is very unlikely for CYP2J2 overexpression to suppress Ang II-induced AAA. A recent study by Cassis et al ( 20 ) demonstrated that Ang II infusionpromoted AAA formation was independent of increases in blood pressure .…”
Section: Discussionmentioning
confidence: 69%
“…The effect of CYP2J2 may involve various mechanisms. Although Ang II clearly elevated blood pressure in this AAA model, and overexpression of CYP2J2 or s-EH inhibitor administration have been reported to lower blood pressure ( 7,8,11 ), it is very unlikely for CYP2J2 overexpression to suppress Ang II-induced AAA. A recent study by Cassis et al ( 20 ) demonstrated that Ang II infusionpromoted AAA formation was independent of increases in blood pressure .…”
Section: Discussionmentioning
confidence: 69%
“…To determine whether EET autacoids produced by the endothelium promote tissue growth, we have generated three lines of transgenic mice with high endothelial EET levels: mice with endothelial (Tie2-promoter driven) expression of either human CYP2C8 or human CYP2J2 (Tie2-CYP2C8-Tr and Tie2-CYP2J2-Tr) and mice with global disruption of the gene that encodes sEH (sEH-null) (19). Tie2-CYP2C8-Tr and Tie2-CYP2J2-Tr mice have significantly increased endothelial EETs compared with wild-type (WT) mice, as measured by liquid chromatography-tandem mass spectrometry (LC-MS/MS) (19,20), and sEH-null mice have significantly increased plasma EETs (21). In contrast, COX-and LOX-derived metabolites are unaffected in these mice (20).…”
Section: Resultsmentioning
confidence: 99%
“…ECs were isolated from WT, Tie2-CYP2J2-Tr, Tie2-CYP2C8-Tr, and Tie2-sEH-Tr mice, and LC-MS/MS analysis was performed as described (19,20,22). All human studies were reviewed and approved by the Institutional Review Board at Lahey Clinic Medical Center.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether EET autacoids produced by the endothelium promote cancer, we generated three lines of transgenic mice with high endothelial EET levels: mice with endothelial (Tie2 promoterdriven) expression of either human CYP2C8 or human CYP2J2 (Tie2-CYP2C8-Tr, Tie2-CYP2J2-Tr) (15) and mice with global disruption of the gene that encodes sEH (sEH-null) (16). ECs isolated from Tie2-CYP2C8-Tr and Tie2-CYP2J2-Tr mice had significantly increased EET levels compared with ECs isolated from WT mice as measured by liquid chromatography-tandem mass spectrometry (LC/MS/MS) (Supplemental Figure 1B), and sEH-null mice have significantly increased plasma EETs compared with WT mice (17).…”
Section: Endothelium-derived Eets Stimulate Primary Tumor Growthmentioning
confidence: 99%